New Knowledge for Old Regions? The Case of the Software Park Hagenberg in the Traditional Industrial Region of Upper Austria - Gunther Maier; Michaela Trippl (European Regional Science Association (ERSA), 2011)
This paper seeks to enhance our understanding about the opportunities and limits of new path creation in traditional regional innovation systems. Due to their inherited historical legacies, such systems are usually thought of being ill-equipped to give rise to high-tech or knowledge intensive activities. Departing from recent insights on research concerned with the transformation of innovation systems and evolutionary economic geography we identify in a conceptual way enabling and constraining factors for the rise of new development paths in traditional regions. Empirically, we focus on the case of the "Software Park Hagenberg" (SPH) located in the old industrial region of Upper Austria. We examine key events triggering the emergence and subsequent evolution of the SPH and explore the role of the RIS in shaping the development trajectory of the SPH. Moreover, applying social network analysis tools, we investigate the pattern of networking between firms, research organisations and educational bodies within the SPH and we provide some evidence on the diffusion of knowledge and innovation generated though these interactions throughout the regional economy.
Keywords: 330